Effect of GMAW-CMT Heat Input on Weld Bead Profile Geometry for Freeform Fabrication of Aluminium Parts - Wagiman, Abdullah; Wahab, Mohd Saidin; Mohid, Zazuli; Mamat, Azuddin (Trans Tech Publications, 2014)
In developing a new method for weld based freeform fabrication, parameter affecting the geometry of single-pass need to be determined as it has great influence on dimensional accuracy and mechanical property of metallic part. In this paper, profile geometry and microstructure of single pass weld bead developed using Gas Metal Arc Welding Cold Metal Transfer (GMAW-CMT) was investigated. Observation on cross sectional weld bead indicates GMAW-CMT has capability to produce free spatter and crack defect weld bead. Profile geometry measurement shows weld bead develop at higher heat input has width size larger than the weld bead develop at lower heat input. Microstructure examination in the substrate reveals formation of columnar dendritic, cellular and planar structure while at buildup layer exhibit equiaxed dendritic structure.